Life cycle of political parties: uncertainty between two constitutional resolutions - Cambronero Torres, Andrei (2023)
This article analyzes how the sentences n.° 09340-2010 and 16592-2011 dictated by the Costa Rican Constitutional Court, relative to the annulment of district assemblies as an obligatory structure and the elimination of the political party’s duty to present candidacies under penalty of deregistration, have impacted the origin, structure and eventual cancellation of political groupings. Among the evaluated points are the influence or lack thereof in the decision of political parties to appear (nationally or cantonally) and the impossibility of deregistration or evaluation if there is enough citizen support to remain in the respective register. In sum, it exposes the collateral effects that these judicial decisions have produced in the electoral system.